Analisis Proses pada Heater Treater dalam Memecah Emulsi di Stasiun Pengumpul (SP) di Lapangan Dep - Asraf, Muh; Anggraini, Devi (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study analyses the performance of the Heater Treater in breaking down oil-water emulsions at the Dep Field Gathering Station. The methods used include field observations, operational data analysis, and documentation studies to evaluate the effectiveness of the two-stage separation process. The results show that the Heater Treater operates optimally at a temperature range of 100-160°F through a combination of thermal heating and electrostatic separation. The electrostatic system proved to be effective in coagulating residual water droplets in the oil phase, while the Level Control Valve played a crucial role in preventing excess water in the oil bucket, which had been set to determine how much water would cause the valve to open automatically. The indicator light on the transformer serves as a marker; if an excess has reached the cathode anode, the indicator light will turn off. This study concludes that the integration of thermal and electrostatic processes in the Heater Treater is an effective solution for handling heavy oil emulsions in production facilities.